Approach and management of diaphragmatic paralysis in adults - Hernández-Gómez, Eli D.; Choncoa-Valderrama, Yazmin; Cruz-Corzo, Luis E.; Cerrillo-Avila, Javier; Sánchez-Reyes, Karina (International Journal of Research in Medical Sciences, 2022)
3 years ago, 38-year-old male, with no relevant personal pathological history, began to present exertional dyspnea, gastroesophageal reflux, retrosternal pyrosis, dyspepsia and postprandial abdominal distension after a traffic accident. A study protocol was initiated, where cabinet studies documented elevation of the left hemidiaphragm was documented. A minimally invasive approach was performed with the finding of elevation of the left hemidiaphragm of approximately 8 cm in relation to the contralateral diaphragm without evidence of paraesophageal hernia. Mayo type left diaphragmatic plication was performed with non-absorbable suture (polypropylene 1) without complications. With favorable evolution, he started the oral route 8 hours postoperatively, and was discharged 48 hours after surgery due to clinical improvement and without gastroesophageal reflux. Surgical plication of the affected hemidiaphragm is successful in carefully selected patients with severe symptoms thought to be due to unilateral diaphragmatic paralysis. Studies demonstrate improvement in several parameters, including lung and respiratory muscle function, exercise endurance, blood gas exchange, and possibly dyspnea.